1996
DOI: 10.1016/s0022-5223(96)70339-2
|View full text |Cite
|
Sign up to set email alerts
|

Transmyocardial laser revascularization: Clinical experience with twelve-month follow-up

Abstract: We are investigating a new technique for myocardial revascularization in which an 800 W carbon dioxide laser is used to drill 1 mm diameter channels into a beating heart after left thoracotomy. Clotting occludes the channels on the subepicardium, and in the long-term setting, blood from the left ventricular cavity flows through these channels to perfuse the ischemic subendocardium. To test the efficacy of this technique in a preliminary clinical trial, we used it as sole therapy for 21 consecutive patients. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
70
1
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(86 citation statements)
references
References 11 publications
11
70
1
4
Order By: Relevance
“…Increased myocardial perfusion, directly through the patent channels or indirectly via laser-induced neovascularization, has been the main proposed mechanism of angina relief. Angina relief has been a consistent finding of most clinical studies 3,5,12,20,21 regardless of the kind of laser used, CO 2 or Ho:YAG. However, increased perfusion, channel patency, and neovascularization have all been very variable findings.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Increased myocardial perfusion, directly through the patent channels or indirectly via laser-induced neovascularization, has been the main proposed mechanism of angina relief. Angina relief has been a consistent finding of most clinical studies 3,5,12,20,21 regardless of the kind of laser used, CO 2 or Ho:YAG. However, increased perfusion, channel patency, and neovascularization have all been very variable findings.…”
Section: Discussionsupporting
confidence: 55%
“…1 Results of clinical studies continue to show that TMR is effective in relieving angina. [2][3][4][5] However, the exact mechanisms by which TMR exerts its effects and relieves angina are still controversial. The main proposed mechanisms include direct blood flow from the ventricular cavity to the ischemic myocardium through laser-created channels 2,6,7 and increased myocardial blood flow through neovascularization mediated by thermal or mechanical laser injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, though several preliminary studies demonstrated a decrease in angina severity in most patients (Cooley et al, 1996;Horvath et al, 1996), subsequent randomized controlled trials (RCT) have reported contradictory results (Aaberge et al, 2000;Burkhoff et al, 1999;Campbell et al, 2001;Jones et al, 1999;March, 1999;van der Sloot et al, 2004). Briones et al (Briones et al, 2009) conducted a Cochrane systematic review to assess the efficacy and safety of TMR versus optimized drug therapy in alleviating angina and improving survival and heart function.…”
Section: Evidencementioning
confidence: 99%
“…Although histological, immunohistochemical and molecular studies in animal models have demonstrated the presence of angiogenesis in the myocardium surrounding the treated region, [3][4][5][6][7] the controversy continues as to whether or not TMLR can enhance myocardial perfusion in clinical settings. [8][9][10][11] Various modalities have been employed to assess myocardial perfusion in the TMLR-treated heart such as the microsphere technique, 3,5 positron emission tomography and Tc-sestamibi scintigraphy. [12][13][14] However, perfusion around an individual laser channel has not been analyzed because the required spatial resolution cannot be achieved through these methods.…”
mentioning
confidence: 99%